2020
DOI: 10.1016/s2215-0366(20)30248-0
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic medication versus psychological intervention versus a combination of both in adolescents with first-episode psychosis (MAPS): a multicentre, three-arm, randomised controlled pilot and feasibility study

Abstract: Background Evidence for the effectiveness of treatments in early-onset psychosis is sparse. Current guidance for the treatment of early-onset psychosis is mostly extrapolated from trials in adult populations. The UK National Institute for Health and Care Excellence has recommended evaluation of the clinical effectiveness and cost-effectiveness of antipsychotic drugs versus psychological intervention (cognitive behavioural therapy [CBT] and family intervention) versus the combination of these treatments for ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 27 publications
2
46
0
1
Order By: Relevance
“…A number of RCTs have been conducted where people with schizophrenia or psychosis are offered CBT as an alternative to antipsychotics, utilising TAU comparator groups. These have included CBT versus antipsychotics (TAU) or a combination of both 13,14 (or a combination of CBT plus family therapy versus antipsychotics or both) 15 . The results of these trials have led some to suggest that ‘patient choice’ should include the use of this intervention in place of antipsychotic medication (cited in the current meta‐analysis).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of RCTs have been conducted where people with schizophrenia or psychosis are offered CBT as an alternative to antipsychotics, utilising TAU comparator groups. These have included CBT versus antipsychotics (TAU) or a combination of both 13,14 (or a combination of CBT plus family therapy versus antipsychotics or both) 15 . The results of these trials have led some to suggest that ‘patient choice’ should include the use of this intervention in place of antipsychotic medication (cited in the current meta‐analysis).…”
mentioning
confidence: 99%
“…All of these trials have been conducted by the same research group (Morrison and colleagues) and have TAU as comparator (with no active psychological placebo). One trial showed a significant difference between CBT and TAU, with 37 people in each arm, 13 one an advantage for CBT plus antipsychotics over CBT alone, 14 and one (feasibility study) showed no difference between psychosocial interventions and TAU in adolescents with psychosis 15 …”
mentioning
confidence: 99%
“…These findings are consistent with the existing qualitative research suggesting a ‘safety net’ of information, strategies and supports is needed to successfully withdraw from antipsychotics. 5 , 18 , 19 , 25 , 27 , 53 However, studies of attempted withdrawal show people frequently lack the information, skills and support needed to build this kind of safety net, 18 , 26 , 52 and often taper off too rapidly, relapse and resume the medication. 11 , 17 , 24 The reverse was true for this group.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 A number of studies suggest that talking therapy and other psycho-social interventions improve outcomes among those who experience psychosis and represent promising alternatives to antipsychotic treatment, but withdrawal research typically overlooks these treatments and their targets as potential covariates. 49 - 54 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation